Principle of globalization, or Venice and Mongols in the Middle Ages: on the book by Nicola di Cosmo and Lorenzo Pubblici - Klyuev A.I. (Золотоордынское обозрение)
This article analyzes the monograph by Italian historians Nicola di Cosmo, Professor of East Asian Studies at the Institute for Advanced Study (Princeton, USA) and Lorenzo Pubblici, Professor at the University of Naples «Orientale» (Italy), devoted to trade and diplomatic relations between the Venetians and Mongols on the Silk Roads in the 13th–15th centuries. Research materials: The monograph by Di Cosmo N., Pubblici L. titled Venezia e i Mongoli. Commercio e diplomazia sulle vie della seta nel medioevo (secoli XIII–XV). Roma: Viella, 2022. 315 p. Novelty and results of the study: In the 13th century, two forces met in the Black Sea: the Venetians, representatives of the dominant maritime republic in the Mediterranean, and the Mongols, masters of vast territories that included China, Persia, Central Asia, and others. In solidarity with the methodological constructs of the American sociologist Janet Abu-Luhod, the authors of the monograph proposed for review consider Mongol power, established in the course of campaigns of conquest, as Pax Mongolica not only in the sense of political organization, but also as a trading subsystem which was purposefully built, on the one hand, by the Mongol rulers, and on the other hand, actively supported by the Venetians in particular. The book consists of two parts. The first part reconstructs the event and political context of the emergence of Mongolian geopolitics out of a multitude of regional political systems and economies that created the necessary conditions for close contact with the Venetians, the main stages of these relationships, and the role of the Black Sea in the history of trade relations between the Mongols and the Venetians. In the second part of the book, the authors analyze the specific mechanisms of trade and diplomatic relations, noting the hard and innovative work of both participants in a huge network. In particular, this section is about the figure of Marco Polo and his journey, touching on the development of navigation, legal aspects of relations, and means of exchange and communication. The review gives a brief characterization of the methodological constructs employed by the authors, considers the content of the work, evaluates individual conclusions of the authors, and concludes on the importance of the two historians’ research.